Hypogammaglobulinaemia in a patient with ring chromosome 21. Issue 3 (1st September 1997) - Ohga, Shouichi; Nakao, Futoshi; Narazaki, Osamu; Fusazaki, Naoki; Aoki, Tomonobu; Kamesaki, Kenji; Hara, Toshiro
Abstract : An 8 year old boy with ring chromosome 21 who was susceptible to sinorespiratory infections due to hypogammaglobulinaemia is reported. He presented with the characteristic features of monosomy 21 syndrome, such as psychomotor retardation, hypertonia, large saccular ears, prominent nasal bridge, micrognathia, thrombocytopenia, and patent ductus arteriosus. His serum IgG concentration was less than 1.5 g/l at 3 years and 6 months of age after repeated hospitalisations with pneumonia, otitis media, and convulsions. Regular replacement of intravenous gammaglobulin effectively reduced such infectious episodes. A predisposition to infection in patients with ring chromosome 21 may be explained by hypogammaglobulinaemia and merit treatment with gammaglobulin.